Ultra-high performance premixed green concrete and preparation method thereof

By using maleic acid modified concave and convex rod soil and cocamidopropyl betaine modified fiber in concrete, the crack resistance and compressive strength of concrete are improved, and the existing concrete lacks performance and high environmental protection are solved. The cost issue achieves a combination of high performance and environmental protection.

CN119241171APending Publication Date: 2025-01-03WUHAN ZHONGYANGMING BUILDING MATERIALS CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411390929.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Existing concrete has insufficient performance in terms of crack resistance and compressive strength, and is environmentally friendly and cost-effective.

Method used

Utilize ultra-high performance ready-mixed green concrete formula, including cement, sand, gravel, fly ash, straw ash, silica fume, nano-silica, polyacrylic emulsion, exciter, defoaming agent, reducer, maleic acid Modified concave and convex rod soil and cocamidopropyl betaine modified fibers improve the crack resistance and compressive strength of concrete through careful selection and proportional materials, while reducing environmental protection costs.

Benefits of technology

It significantly improves the mechanical properties and durability of concrete, reduces the carbon footprint of the construction industry, meets the requirements of sustainable development, is easy to operate and mass production, and improves the quality and efficiency of construction projects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses ultrahigh-performance premixed green concrete and a preparation method thereof. The concrete comprises the following raw materials in parts by mass: 375-430 parts of cement; 670 to 729 parts of sand; 830 to 900 parts of broken stone; 60 to 75 parts of fly ash; 45 to 55 parts of straw ash; 25 to 30 parts of silica fume; 10 to 15 parts of nano silicon dioxide; 30 to 55 parts of polyacrylic acid emulsion; 120 to 125 parts of water; 8-11 parts of a water reducing agent; 7-11 parts of an exciting agent; 1.5 to 2.3 parts of a defoaming agent; 7-10 parts of a shrinkage reducing agent; 13 to 20 parts of maleic acid modified attapulgite; 26 to 40 parts of cocamidopropyl betaine modified fiber; the cocamidopropyl betaine modified fibers are prepared by modifying fibers with cocamidopropyl betaine, and the cocamidopropyl betaine modified fibers are prepared from cocamidopropyl betaine; the fiber is selected from at least one of coconut fiber and ramie fiber. The concrete provided by the invention has the advantages of environmental protection, strong crack resistance and relatively high compressive strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of building materials, and in particular to an ultra-high performance premixed green concrete and a preparation method thereof. Background Art

[0002] With the rapid development of the construction industry, concrete, as the most important building material, has received increasing attention for its performance and environmental friendliness. Although traditional concrete has high strength, it still needs to be improved in terms of durability and crack resistance. At the same time, with the improvement of environmental awareness, the development of green, environmentally friendly, and high-performance concrete materials has become an important direction for the development of the industry. Currently, high-performance concrete on the market mostly uses special additives and reinforcing materials to improve performance, but they are often costly and environmentally unfriendly. Therefore, how to achieve environmental protection and cost control while ensuring the high performance of concrete has become an urgent problem to be solved in this field. Summary of the invention

[0003] In order to solve at least one of the above technical problems and develop an environmentally friendly concrete with strong crack resistance and high compressive strength, the present application provides an ultra-high performance premixed green concrete and a preparation method thereof.

[0004] In a first aspect, the present application provides an ultra-high performance premixed green concrete, the concrete comprising the following raw materials in parts by weight: 375-430 parts of cement; Sand 670-729 parts; 830-900 parts of crushed stone; 60-75 parts of fly ash; 45-55 parts of straw ash; Silica fume 25-30 parts; 10-15 parts of nano silicon dioxide; 30-55 parts of polyacrylic acid emulsion; 120-125 parts of water; Water reducing agent 8-11 parts; 7-11 parts of stimulant; 1.5-2.3 parts of defoaming agent; 7-10 parts of shrinkage reducing agent; 13-20 parts of maleic acid modified attapulgite; 26-40 parts of cocamidopropyl betaine modified fiber; The cocamidopropyl betaine modified fiber is prepared by modifying the fiber with cocamidopropyl betaine; and the fiber is selected from at least one of coconut shell fiber and ramie fiber.

[0005] By adopting the above technical solution, this application proposes an ultra-high performance premixed green concrete and its preparation method, aiming to solve the technical problems existing in existing concrete, such as insufficient environmental protection, poor crack resistance and low compressive strength. The concrete formula aims to provide a solution that is both environmentally friendly and can significantly improve the performance of concrete by carefully selecting and proportioning a variety of raw materials. Specifically, the concrete contains the following main ingredients: cement as the basic cementitious material, responsible for the basic strength formation of concrete; sand and gravel as aggregates, enhancing the stability and overall strength of concrete; fly ash as an industrial by-product, can improve the working performance of concrete and enhance its durability; straw ash as agricultural waste, not only helps to enhance the crack resistance of concrete, but also increases the environmental protection attributes of the product; silica fume and nano-silica as fine fillers, can significantly improve the density and strength of concrete; polyacrylic acid emulsion is used to improve the bonding performance of concrete and reduce permeability; water reducer can reduce water consumption while maintaining or improving the fluidity of concrete; activator can promote the early hydration reaction of cementitious materials and accelerate the hardening process of concrete; defoamer is used to eliminate bubbles generated during mixing and improve the density of concrete; shrinkage reducer helps to reduce concrete shrinkage and reduce the risk of cracking; cocamidopropyl betaine modified fiber and maleic acid modified attapulgite are two key ingredients, which play an important role in improving the crack resistance and compressive strength of concrete. Cocamidopropyl betaine modified fiber is a specially modified natural fiber derived from plant fibers such as coconut shell fiber or ramie fiber. After surface modification with cocamidopropyl betaine, this fiber can be better dispersed in concrete and enhance the interfacial bonding between the fiber and the concrete matrix. This modified fiber can effectively inhibit the development of cracks inside concrete, thereby significantly improving the crack resistance of concrete. In addition, the presence of fiber can also improve the toughness of concrete, so that concrete can better absorb energy when subjected to external forces, thereby improving its compressive strength. Maleic acid-modified attapulgite is a natural mineral material modified by maleic acid. This modified attapulgite can better interact with other components in concrete, especially in the cement hydration process. Maleic acid-modified attapulgite can improve the microstructure of concrete and increase its density, thereby significantly improving the impermeability and freeze-thaw resistance of concrete. In addition, it can also improve the overall strength and crack resistance of concrete by improving the microstructure of concrete and reducing porosity.

[0006] Through the above technical solution, the ultra-high performance premixed green concrete provided by this application not only has excellent mechanical properties and durability, but also performs well in environmental protection, can effectively reduce the carbon footprint of the construction industry, and meets the requirements of sustainable development. In addition, the concrete is easy to operate during the preparation process, convenient for large-scale production and construction application, which is of great significance for improving the quality and efficiency of construction projects.

[0007] Optionally, the preparation method of the maleic acid modified attapulgite is as follows: add the attapulgite into a calcining furnace, calcine at 300-400°C for 3-4 hours, and then crush it. Take 10-20 parts of the crushed attapulgite by weight and add them to 30-50 parts of maleic acid solution, stir and treat at 80-100°C for 60-90 minutes, then separate by sedimentation, wash and dry the solid matter to obtain maleic acid modified attapulgite.

[0008] By adopting the above technical scheme, maleic acid-modified attapulgite can significantly improve the crack resistance and compressive strength of concrete. Specifically, the attapulgite is first calcined at a temperature of 300-400°C for 3-4 hours. This process helps to remove moisture and other volatile substances in the attapulgite and improve its activity. It is then crushed and added to a maleic acid solution, and stirred at a temperature of 80-100°C for 60-90 minutes. This treatment process allows the maleic acid molecules to penetrate deeper into the microporous structure of the attapulgite, and the attapulgite is modified by chemical reaction, thereby improving its compatibility and interfacial bonding with other components in the concrete. The maleic acid-modified attapulgite obtained after sedimentation separation, washing and drying can be more evenly distributed in the concrete due to its optimized surface properties, effectively improving the microstructure of the concrete, reducing the porosity, and increasing the density of the concrete. This modified attapulgite can also enhance the impermeability and freeze-thaw resistance of the concrete, thereby significantly improving the overall strength and durability of the concrete. The maleic acid-modified attapulgite prepared in this way can not only effectively improve the crack resistance of concrete, but also enhance its compressive strength, meeting the strict requirements of high-performance concrete, while also embodying the concept of green environmental protection.

[0009] Optionally, the mass concentration of the maleic acid solution is 30-40%.

[0010] Optionally, the fiber is made by mixing coconut shell fiber and ramie fiber in a weight ratio of 1:1.

[0011] By adopting the above technical solution, that is, mixing coconut shell fiber and ramie fiber in a weight ratio of 1:1, the fiber obtained can significantly improve the crack resistance and compressive strength of concrete. Specifically, this mixed fiber takes advantage of the respective advantages of coconut shell fiber and ramie fiber: coconut shell fiber has good corrosion resistance and high strength, while ramie fiber has good flexibility and high elastic modulus. Mixing these two fibers in a ratio of 1:1 can make full use of their complementary advantages and improve the uniformity and complexity of the fiber network inside the concrete. This mixed fiber can be more evenly dispersed in the concrete, effectively inhibiting the occurrence and development of cracks inside the concrete, thereby significantly improving the crack resistance of the concrete. In addition, the addition of mixed fibers can also increase the toughness of concrete, so that it can better absorb energy when subjected to external forces, thereby improving the compressive strength of concrete. The fibers prepared in this way can not only significantly improve the performance of concrete, but also embody the effective use of resources and environmental protection concepts, which meet the development needs of high-performance concrete.

[0012] Optionally, the cocamidopropyl betaine modified coconut shell fiber is prepared from fiber, sodium hydroxide, cocamidopropyl betaine, dopamine hydrochloride and solvent in a weight ratio of (10-15):(4-7):(125-140):(0.5-0.8):(65-85).

[0013] By adopting the above technical scheme, coconut shell fiber modified with cocamidopropyl betaine can significantly improve the crack resistance and compressive strength of concrete. Specifically, this modified fiber utilizes the high strength and good corrosion resistance of coconut shell fiber itself, and enhances the interfacial bonding force between the fiber and the concrete matrix through surface modification treatment with cocamidopropyl betaine. The sodium hydroxide used in the modification process can pre-activate the fiber surface and promote the adsorption of subsequent modifiers; and dopamine hydrochloride, as a bioadhesive, can form a stable polymer coating on the fiber surface, further improving the bonding performance between the fiber and the concrete matrix. This modified fiber can be more evenly dispersed in concrete, effectively inhibiting the occurrence and development of cracks inside the concrete, thereby significantly improving the crack resistance of concrete. In addition, the addition of modified fibers can also increase the toughness of concrete, so that concrete can better absorb energy when subjected to external forces, thereby improving the compressive strength of concrete. The modified fiber prepared in this way can not only significantly improve the performance of concrete, but also embodies the effective utilization of resources and environmental protection concepts, which meets the development needs of high-performance concrete.

[0014] Optionally, the solvent is selected from a mixture of TrisHCl buffer and anhydrous ethanol, wherein the weight ratio of the TrisHCl buffer to the anhydrous ethanol is 1:2.

[0015] Optionally, the preparation method of the cocamidopropyl betaine modified coconut shell fiber is as follows: A1, boiling the fiber with a sodium hydroxide aqueous solution, and then mixing with a solvent to prepare a first mixed solution; A2. Mix cocamidopropyl betaine and dopamine hydrochloride, add the first mixed solution, stir and polymerize at 37° C. for 1-2 days, rinse and dry to obtain cocamidopropyl betaine modified fiber.

[0016] By adopting the above technical scheme, coconut shell fiber is first boiled with sodium hydroxide aqueous solution to activate the fiber surface, and then mixed with a solvent to obtain a first mixed solution; then cocamidopropyl betaine and dopamine hydrochloride are mixed and added to the first mixed solution, stirred and polymerized at 37°C for 1-2 days, and then rinsed and dried to finally obtain modified fiber. This modified fiber can significantly improve the crack resistance of concrete, because cocamidopropyl betaine, as a surfactant, can improve the interfacial bonding between the fiber and the concrete matrix, and dopamine hydrochloride can enhance the adhesion of the fiber through its unique self-assembly and cross-linking ability, thereby improving the toughness of concrete. Maleic acid-modified attapulgite is prepared through a specific heat treatment and chemical modification process. This method can optimize the surface properties of attapulgite, improve its compatibility with other components in concrete, and then improve the microstructure of concrete, improve its density and impermeability, and ultimately enhance the compressive strength and durability of concrete.

[0017] Optionally, the weight ratio of the maleic acid modified attapulgite to the cocamidopropyl betaine modified fiber is 1:(1.8-2.4).

[0018] By adopting the above technical solution, by mixing these two key ingredients in a weight ratio of 1: (1.8-2.4), their respective advantages can be fully utilized and synergistically act in concrete, effectively inhibiting the occurrence and development of cracks inside the concrete, and significantly improving the crack resistance and compressive strength of the concrete. In addition, the selection of this mix ratio also helps to optimize cost-effectiveness, ensuring that the concrete not only has excellent performance, but also performs well in terms of economy and environmental protection, which meets the development needs of high-performance concrete.

[0019] Optionally, the total weight of the maleic acid modified attapulgite and the cocamidopropyl betaine modified fiber accounts for 1.6-2.5% of the total weight of the concrete.

[0020] In a second aspect, the present application provides a method for preparing ultra-high performance premixed green concrete, the method for preparing the concrete comprising the following steps: S1, the water is divided into three equal parts, the first part of the water is mixed with the water reducing agent to obtain the first mixed solution, and the second part of the water is mixed with the shrinkage reducing agent and the defoaming agent to obtain the second mixed solution; S2, cement, sand, gravel, fly ash, straw ash, silica fume, the third portion of water, and polypropylene solution are mixed in order, placed in a pan mixer, and stirred for 1 min; then cocamidopropyl betaine modified fiber and maleic acid modified attapulgite are added, stirred for 2-4 min, and then the first portion of the mixed solution prepared in step S1 is added, stirred for 3-5 min, and the third portion of the mixed solution is prepared; S3, add the activator to the third mixed solution, stir evenly for 3-5 minutes, and obtain the fourth mixed solution; S4. Add the second mixed liquid to the fourth mixed liquid, stir for another 23 minutes until the mixture is uniform, discharge the mixture to obtain a concrete mixture, and shape and cure the concrete mixture to obtain the ultra-high performance premixed green concrete.

[0021] By adopting the above technical solution, the preparation method of the present application can ensure that various additives and reinforcing materials are fully dispersed and evenly mixed, thereby significantly improving the crack resistance and compressive strength of concrete. In addition, by accurately controlling the operating conditions of each step, such as mixing time and addition order, the working performance of concrete can be effectively improved, energy consumption can be reduced, and the impact of concrete on the environment during the production process can be reduced, which is in line with the development trend and environmental protection requirements of high-performance concrete.

[0022] In summary, the present invention includes at least one of the following beneficial technical effects: 1. The ultra-high performance premixed green concrete provided in this application not only has excellent mechanical properties and durability, but also performs well in environmental protection, can effectively reduce the carbon footprint of the construction industry, and meets the requirements of sustainable development. In addition, the concrete is easy to operate during the preparation process, convenient for large-scale production and construction application, and is of great significance for improving the quality and efficiency of construction projects.

[0023] 2. Cocoamidopropyl betaine modified coconut shell fiber can significantly improve the crack resistance and compressive strength of concrete. Specifically, this modified fiber takes advantage of the high strength and good corrosion resistance of coconut shell fiber itself, and enhances the interfacial bonding between the fiber and the concrete matrix through surface modification treatment with cocamidopropyl betaine. The sodium hydroxide used in the modification process can pre-activate the fiber surface and promote the adsorption of subsequent modifiers; while dopamine hydrochloride, as a bioadhesive, can form a stable polymer coating on the fiber surface, further improving the bonding performance between the fiber and the concrete matrix. This modified fiber can be more evenly dispersed in concrete, effectively inhibiting the occurrence and development of cracks inside the concrete, thereby significantly improving the crack resistance of concrete. In addition, the addition of modified fibers can also increase the toughness of concrete, so that the concrete can better absorb energy when subjected to external forces, thereby improving the compressive strength of concrete. The modified fiber prepared in this way can not only significantly improve the performance of concrete, but also embodies the effective utilization of resources and environmental protection concepts, which meets the development needs of high-performance concrete.

[0024] 3. Maleic acid-modified attapulgite can significantly improve the crack resistance and compressive strength of concrete. Specifically, the attapulgite is first calcined at 300-400°C for 3-4 hours. This process helps to remove moisture and other volatile substances in the attapulgite and improve its activity. It is then crushed and added to a maleic acid solution and stirred at 80-100°C for 60-90 minutes. This treatment process allows the maleic acid molecules to penetrate deeper into the microporous structure of the attapulgite, and the attapulgite is modified through chemical reactions, thereby improving its compatibility and interfacial bonding with other components in the concrete. The maleic acid-modified attapulgite obtained after sedimentation separation, washing and drying can be more evenly distributed in the concrete due to its optimized surface properties, effectively improving the microstructure of the concrete, reducing the porosity and increasing the density of the concrete. This modified attapulgite can also enhance the impermeability and freeze-thaw resistance of concrete, thereby significantly improving the overall strength and durability of concrete. The maleic acid-modified attapulgite prepared in this way can not only effectively improve the crack resistance of concrete, but also enhance its compressive strength, meeting the strict requirements of high-performance concrete, while also embodying the concept of green environmental protection.

[0025] 4. The preparation method of the present application can ensure that various additives and reinforcing materials are fully dispersed and evenly mixed, thereby significantly improving the crack resistance and compressive strength of concrete. In addition, by precisely controlling the operating conditions of each step, such as mixing time and addition order, it can effectively improve the working performance of concrete, reduce energy consumption, and reduce the impact of concrete on the environment during the production process, which is in line with the development trend and environmental protection requirements of high-performance concrete. DETAILED DESCRIPTION

[0026] The present application is further described in detail below with reference to the embodiments.

[0027] Cement: P.052.5 grade ordinary Portland cement, Dongsheng Building Materials Business Department, Shawan District, Leshan City.

[0028] Sand: The sand is made of hard river sand and well-graded high-quality quartz sand in a mass ratio of 9:1. The river sand fineness modulus is 2.8-3.0, the silica content in the quartz sand is not less than 98%, the particle size is 0.3-0.6mm, and the density is 2.62g / cm 3 .

[0029] Crushed stone: The crushed stone is selected from limestone and basalt crushed stone with good gradation, compactness, hardness and rough surface in a mass ratio of 1:1, with a particle size range of 5mm-15mm. The crushed stone of continuous particle size of 5-10mm and 10-15mm is mixed in a mass ratio of 7:3.

[0030] Fly ash: Lingshou County Shengtong Mineral Products Business Department, particle size 0.005-0.05mm. Density 2.45g / cm 3 .

[0031] Straw ash: Guangxi Zhuangfang Liyuan Biotechnology Co., Ltd., moisture 1%.

[0032] Silica fume: Hebei Houkang Mineral Products Co., Ltd., specific surface area 20-28m 2 / g.

[0033] Nano silicon dioxide: CAS number is 7631-86-9, content is 99.9%, model is DK-SiO2-15.

[0034] Polyacrylic acid emulsion: Jinan Feiyue Chemical Co., Ltd., the active ingredient content is 99%.

[0035] Water reducer: Polycarboxylate water reducer, Henan Mingzhixin Chemical Products Co., Ltd., solid content 99% Activator: Sodium sulfate, Tianjin Jinhui Taiya Chemical Reagent Co., Ltd., content 98%.

[0036] Defoamer: Polyether defoamer: Shandong Meiyu Chemical Co., Ltd., model P-06.

[0037] Shrinkage reducing agent: Guangxi Hengyong Building Materials Co., Ltd., model HY-1KN.

[0038] Maleic acid: CAS No. 110-16-7, purity 99.9%.

[0039] Attapulgite: CAS No. 1337-76-4, purity 98%.

[0040] Cocamidopropyl Betaine: CAS No. 61789-40-0, purity 99%.

[0041] Coconut shell fiber: Machi Electronics, Licheng District, Jinan City, item number cwMAyWTp.

[0042] Ramie fiber: length is 40-50mm.

[0043] Example 1 The present embodiment provides an ultra-high performance premixed green concrete, comprising the following raw materials in parts by weight: 375 parts of cement; 670 parts of sand; 830 parts of crushed stone; 60 parts of fly ash; 45 parts of straw ash; 25 parts of silica fume; 10 parts of nano silicon dioxide; 30 parts of polyacrylic acid emulsion; 120 parts of water; 8 parts of water reducer; 7 parts of activator; 1.5 parts of defoamer; 7 parts of shrinkage reducer; 13 parts of maleic acid modified attapulgite; 26 parts of cocamidopropyl betaine modified fiber; The water reducing agent in this embodiment is a polycarboxylic acid water reducing agent.

[0044] The cement in this embodiment is P.052.5 grade ordinary Portland cement.

[0045] The crushed stone particle size range in this embodiment is 5mm-15mm, and the crushed stones of continuous particle sizes of 5-10mm and 10-15mm are mixed in a mass ratio of 7:3.

[0046] The stimulator in this embodiment is sodium sulfate.

[0047] The defoamer in this embodiment is a polyether defoamer.

[0048] The shrinkage reducing agent in this embodiment is HY-1KN type shrinkage reducing agent.

[0049] The cocamidopropyl betaine modified fiber is prepared by modifying the fiber with cocamidopropyl betaine; the fiber is coconut shell fiber; The preparation method of maleic acid modified attapulgite is as follows: add attapulgite into a calcining furnace, calcine at 300°C for 3 hours, then crush, take 10 parts of crushed attapulgite by weight and add them to 30 parts of maleic acid solution, stir at 80°C for 60 minutes, then settle and separate, wash and dry the solid matter to obtain maleic acid modified attapulgite. The mass concentration of the maleic acid solution is 30%.

[0050] The preparation method of cocamidopropyl betaine modified coconut shell fiber is as follows: A1, boiling the fiber with a sodium hydroxide aqueous solution, and then mixing with a solvent to prepare a first mixed solution; A2. Mix cocamidopropyl betaine and dopamine hydrochloride, add the first mixed solution, stir and polymerize at 37° C. for 1 day, rinse and dry to obtain cocamidopropyl betaine modified fiber.

[0051] A method for preparing ultra-high performance premixed green concrete comprises the following steps: S1, the water is divided into three equal parts, the first part of the water is mixed with the water reducing agent to obtain the first mixed solution, and the second part of the water is mixed with the shrinkage reducing agent and the defoaming agent to obtain the second mixed solution; S2, cement, sand, gravel, fly ash, straw ash, silica fume, the third portion of water, and polypropylene solution are mixed in order, placed in a pan mixer, and stirred for 1 min; then cocamidopropyl betaine modified fiber and maleic acid modified attapulgite are added, stirred for 2 min, and then the first portion of the mixed solution prepared in step S1 is added, stirred for 3 min, to prepare the third portion of the mixed solution; S3, add the activator to the third mixed solution, stir evenly for 3-5 minutes, and obtain the fourth mixed solution; S4. Add the second mixed liquid to the fourth mixed liquid, stir for another 2 minutes until the mixture is uniform, discharge the mixture to obtain a concrete mixture, and shape and cure the concrete mixture to obtain the ultra-high performance premixed green concrete.

[0052] Example 2 The difference between this embodiment and embodiment 1 is that, when preparing ultra-high performance premixed green concrete, the weight ratio of maleic acid modified attapulgite to cocamidopropyl betaine modified fiber is 1:1.8.

[0053] Example 3 The difference between this embodiment and embodiment 1 is that, when preparing ultra-high performance premixed green concrete, the weight ratio of maleic acid modified attapulgite to cocamidopropyl betaine modified fiber is 1:2.2.

[0054] Example 4 The difference between this embodiment and embodiment 1 is that, when preparing ultra-high performance premixed green concrete, the weight ratio of maleic acid modified attapulgite to cocamidopropyl betaine modified fiber is 1:2.4.

[0055] Comparative Examples 1-3 Comparative Example 1 The difference between this comparative example and Example 1 is that when preparing the ultra-high performance premixed green concrete, an equal amount of maleic acid-modified attapulgite is used instead of the cocamidopropyl betaine modified fiber.

[0056] Comparative Example 2 The difference between this comparative example and Example 1 is that when preparing the ultra-high performance premixed green concrete, an equal amount of cocamidopropyl betaine modified fiber is used to replace the maleic acid modified attapulgite.

[0057] Comparative Example 3 The difference between this comparative example and Example 1 is that when preparing the ultra-high performance premixed green concrete, an equal amount of fiber is used instead of the cocamidopropyl betaine modified fiber.

[0058] Experimental testing: 1. Compressive strength and flexural strength: According to GB / T500812019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete", the compressive strength and flexural strength of the samples are tested.

[0059] 2. Freeze-thaw cycle: According to GB / T50082-2009 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete", freeze-thaw cycles are performed on the specimens, and the cracking conditions of the specimens before and after the freeze-thaw cycles are tested.

[0060] The experimental test results of Examples 1-4 and Comparative Examples 1-3 are shown in Table 1.

[0061] Table 1 - Experimental test results of Examples 1-4 and Comparative Examples 1-3 Example Compressive strength (28d) Flexural strength Before freeze-thaw cycle Freeze-thaw cycles 300 times Freeze-thaw cycles 600 times Example 1 135.6 35.99 No cracks No cracks No cracks Example 2 133..4 33.12 No cracks No cracks No cracks Example 3 134.2 34.79 No cracks No cracks No cracks Example 4 133.9 34.46 No cracks No cracks No cracks Comparative Example 1 121.3 31.65 No cracks No cracks There are cracks Comparative Example 2 124.1 27.13 There are cracks There are cracks There are cracks Comparative Example 3 122.8 26.53 There are cracks There are cracks There are cracks Result analysis: The difference between Example 2-4 and Example 1 is that when preparing ultra-high performance premixed green concrete, the weight ratio of maleic acid-modified attapulgite and cocamidopropyl betaine modified fiber is different. Combined with the experimental test data in Table 1, it can be seen that when the weight ratio of maleic acid-modified attapulgite and cocamidopropyl betaine modified fiber is 1:2, the comprehensive performance of the ultra-high performance premixed green concrete obtained is better. The difference between Comparative Example 1 and Example 1 is that when preparing ultra-high performance premixed green concrete, an equal amount of maleic acid-modified attapulgite is used to replace cocamidopropyl betaine modified fiber. The difference between Comparative Example 2 and Example 1 is that when preparing ultra-high performance premixed green concrete, an equal amount of cocamidopropyl betaine modified fiber is used to replace maleic acid-modified attapulgite. It can be seen from the experimental test data in Table 1 that when cocamidopropyl betaine modified fiber and maleic acid modified attapulgite are used simultaneously, the compressive strength and crack resistance of concrete are significantly improved. The difference between Comparative Example 3 and Example 1 is that when preparing ultra-high performance premixed green concrete, an equal amount of fiber is used to replace cocamidopropyl betaine modified fiber. It can be seen from the experimental test data in Table 1 that when using instead of cocamidopropyl betaine modified fiber, the compressive strength and crack resistance of concrete will be affected.

[0062] Embodiment 5-6 Example 5 The difference between this embodiment and embodiment 1 is that when preparing ultra-high performance ready-mixed green concrete, the weight percentages of some components are changed. The differences are shown in Table 2.

[0063] Table 2 - Differences between Example 5-6 and Example 1 Ingredients (portions) Example 1 Example 5 Example 6 cement 375 415 430 sand 670 700 729 gravel 830 875 900 Fly ash 60 70 75 Straw ash 45 52 55 Silica Fume 25 28 30 Nano Silica 10 13 15 Polyacrylic acid emulsion 30 48 55 water 120 123 125 Water reducing agent 8 9 11 Stimulant 7 10 11 Defoaming agent 1.5 2.0 2.3 Shrinkage reducing agent 7 8 10 Maleic acid modified attapulgite 16 16 16 Cocamidopropyl Betaine Modified Fiber 32 32 32 The experimental test results of Examples 5-6 are shown in Table 3.

[0064] Table 3 - Experimental test results of Examples 5-6 Example Compressive strength (28d) Flexural strength Before freeze-thaw cycle Freeze-thaw cycles 300 times Freeze-thaw cycles 600 times Example 1 135.6 35.99 No cracks No cracks No cracks Example 5 137.9 36.75 No cracks No cracks No cracks Example 6 136.3 36.14 No cracks No cracks No cracks Result analysis: The difference between Example 5-6 and Example 1 is that when preparing ultra-high performance premixed green concrete, the weight proportions of some components are different. Combined with the experimental test results in Table 3, it can be seen that the comprehensive performance of the ultra-high performance premixed green concrete prepared by Example 5 is better.

[0065] Embodiment 7-11 The difference between Examples 7-11 and Example 5 is that when preparing ultra-high performance premixed green concrete, on the premise that the weight ratio of maleic acid-modified attapulgite and cocoamidopropyl betaine modified fiber is 1:2, the total weight ratio of maleic acid-modified attapulgite and cocoamidopropyl betaine modified fiber in the ultra-high performance premixed green concrete is changed, and the optimal weight ratio is selected.

[0066] In Example 5, the total weight of maleic acid-modified attapulgite and cocamidopropyl betaine-modified fiber is 48 parts, and the total weight of ultra-high performance premixed green concrete is 2401 parts.

[0067] Therefore, it is not difficult to conclude that in Example 5, the proportion of maleic acid modified attapulgite (referred to as variable 1) and cocamidopropyl betaine modified fiber (referred to as variable 2) in the ultra-high performance ready-mixed green concrete (referred to as the matrix) is 2%.

[0068] The differences between Examples 7-11 and Example 5 are shown in Table 4.

[0069] Proportion = (variable 1 + variable 2) / total weight of matrix * 100%.

[0070] Table 4 - Differences between Examples 7-11 and Example 5 The experimental test results of Examples 7-11 are shown in Table 5.

[0071] Table 5 - Experimental test results of Examples 7-11 Result analysis: The difference between Example 7-11 and Example 5 is that when preparing ultra-high performance premixed green concrete, the total weight of maleic acid-modified attapulgite and cocamidopropyl betaine modified fiber in ultra-high performance premixed green concrete accounts for different proportions. Combined with the experimental test results in Table 5, it can be seen that when the total weight of maleic acid-modified attapulgite and cocamidopropyl betaine modified fiber in ultra-high performance premixed green concrete accounts for 1.6-2.5%, the comprehensive performance of the obtained ultra-high performance premixed green concrete is better, and when the total weight of maleic acid-modified attapulgite and cocamidopropyl betaine modified fiber in ultra-high performance premixed green concrete accounts for 2.37%, the comprehensive performance of the obtained ultra-high performance premixed green concrete is the best. When the proportion is too high or too low, the comprehensive performance is reduced.

[0072] Examples 12-13 Example 12 The difference between this embodiment and embodiment 10 is that when preparing ultra-high performance premixed green concrete, the preparation parameters of the cocamidopropyl betaine modified fiber used are different. The preparation method of the cocamidopropyl betaine modified fiber in this embodiment is as follows: The preparation method of maleic acid modified attapulgite is as follows: add attapulgite into a calcining furnace, calcine at 350°C for 3.5 hours, then crush, take 18 parts of crushed attapulgite by weight, add it to 45 parts of maleic acid solution, stir and treat at 95°C for 80 minutes, then settle and separate, wash and dry the solid matter to obtain maleic acid modified attapulgite. The mass concentration of the maleic acid solution is 35%.

[0073] The preparation method of cocamidopropyl betaine modified coconut shell fiber is as follows: A1, boiling the fiber with a sodium hydroxide aqueous solution, and then mixing with a solvent to prepare a first mixed solution; A2. Mix cocamidopropyl betaine and dopamine hydrochloride, add the first mixed solution, stir and polymerize at 37° C. for 1.5 days, rinse and dry to obtain cocamidopropyl betaine modified fiber.

[0074] Example 13 The difference between this embodiment and embodiment 10 is that, when preparing ultra-high performance premixed green concrete, the preparation method of the cocamidopropyl betaine modified fiber in this embodiment is as follows: The preparation method of maleic acid modified attapulgite is as follows: add attapulgite into a calcining furnace, calcine at 400°C for 4 hours, then crush, take 20 parts of crushed attapulgite by weight and add them to 50 parts of maleic acid solution, stir and treat at 100°C for 90 minutes, then settle and separate, wash and dry the solid matter to obtain maleic acid modified attapulgite. The mass concentration of the maleic acid solution is 40%.

[0075] The preparation method of cocamidopropyl betaine modified coconut shell fiber is as follows: A1, boiling the fiber with a sodium hydroxide aqueous solution, and then mixing with a solvent to prepare a first mixed solution; A2. Mix cocamidopropyl betaine and dopamine hydrochloride, add the first mixed solution, stir and polymerize at 37° C. for 2 days, rinse and dry to obtain cocamidopropyl betaine modified fiber.

[0076] Embodiment 14 The difference between this embodiment and embodiment 12 is that when preparing ultra-high performance premixed green concrete, the fiber in this embodiment is a compound of coconut shell fiber and ramie fiber in a weight ratio of 1:1.

[0077] Table 6 - Experimental test results of Examples 12-16 Example Compressive strength (28d) Flexural strength Before freeze-thaw cycle Freeze-thaw cycles 300 times Freeze-thaw cycles 600 times Example 10 139.6 37.84 No cracks No cracks No cracks Example 12 140.9 38.59 No cracks No cracks No cracks Example 13 140..5 38.27 No cracks No cracks No cracks Embodiment 14 141.9 39.88 No cracks No cracks No cracks Result analysis: The difference between Examples 12-13 and Example 10 is that when preparing ultra-high performance premixed green concrete, different preparation parameters are used for the cocamidopropyl betaine-modified coconut shell fiber and maleic acid-modified attapulgite. Combined with the experimental test results in Table 6, it can be seen that the ultra-high performance premixed green concrete prepared by Example 12 has better comprehensive performance.

[0078] The difference between Example 14 and Example 12 is that when preparing ultra-high performance premixed green concrete, the fiber is prepared by compounding coconut shell fiber and ramie fiber. Combined with the experimental test data in Table 6, it can be seen that the cocamidopropyl betaine modified coconut shell fiber prepared from the composite fiber can better improve the compressive strength of the prepared concrete.

[0079] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. An ultra-high performance premixed green concrete, characterized in that: The concrete comprises the following raw materials in parts by weight: 375-430 parts of cement; Sand 670-729 parts; 830-900 parts of crushed stone; 60-75 parts of fly ash; 45-55 parts of straw ash; Silica fume 25-30 parts; 10-15 parts of nano silicon dioxide; 30-55 parts of polyacrylic acid emulsion; 120-125 parts of water; Water reducing agent 8-11 parts; 7-11 parts of stimulant; 1.5-2.3 parts of defoaming agent; 7-10 parts of shrinkage reducing agent; 13-20 parts of maleic acid modified attapulgite; 26-40 parts of cocamidopropyl betaine modified fiber; The cocamidopropyl betaine modified fiber is prepared by modifying the fiber with cocamidopropyl betaine; and the fiber is selected from at least one of coconut shell fiber and ramie fiber.

2. The ultra-high performance ready-mixed green concrete according to claim 1, characterized in that: The preparation method of the maleic acid modified attapulgite is as follows: adding attapulgite to a calcining furnace, calcining at 300-400° C. for 3-4 hours, and then crushing it. By weight, 10-20 parts of the crushed attapulgite are added to 30-50 parts of a maleic acid solution, stirring at 80-100° C. for 60-90 minutes, and then settling and separating. The solid matter is washed and dried to obtain the maleic acid modified attapulgite.

3. The ultra-high performance premixed green concrete according to claim 2, characterized in that: The mass concentration of the maleic acid solution is 30-40%.

4. The ultra-high performance premixed green concrete according to claim 1, characterized in that: The fiber is prepared by mixing coconut shell fiber and ramie fiber in a weight ratio of 1:

1.

5. The ultra-high performance ready-mixed green concrete according to claim 1, characterized in that: The cocamidopropyl betaine modified coconut shell fiber is prepared from fiber, sodium hydroxide, cocamidopropyl betaine, dopamine hydrochloride and solvent in a weight ratio of (10-15): (4-7): (125-140): (0.5-0.8): (65-85).

6. The ultra-high performance ready-mixed green concrete according to claim 5, characterized in that: The solvent is selected from a mixture of TrisHCl buffer and anhydrous ethanol, wherein the weight ratio of the TrisHCl buffer to the anhydrous ethanol is 1:

2.

7. The ultra-high performance ready-mixed green concrete according to claim 1, characterized in that: The preparation method of the cocamidopropyl betaine modified coconut shell fiber is as follows: A1, boiling the fiber with a sodium hydroxide aqueous solution, and then mixing with a solvent to prepare a first mixed solution; A2. Mix cocamidopropyl betaine and dopamine hydrochloride, add the first mixed solution, stir and polymerize at 37° C. for 1-2 days, rinse and dry to obtain cocamidopropyl betaine modified fiber.

8. The ultra-high performance ready-mixed green concrete according to claim 1, characterized in that: The weight ratio of the maleic acid modified attapulgite to the cocamidopropyl betaine modified fiber is 1:(1.8-2.4).

9. The ultra-high performance ready-mixed green concrete according to claim 1, characterized in that: The total weight of the maleic acid modified attapulgite and the cocamidopropyl betaine modified fiber accounts for 1.6-2.5% of the total weight of the concrete.

10. A method for preparing the ultra-high performance premixed green concrete according to any one of claims 1 to 9, characterized in that: The method for preparing the concrete comprises the following steps: S1, the water is divided into three equal parts, the first part of the water is mixed with the water reducing agent to obtain the first mixed solution, and the second part of the water is mixed with the shrinkage reducing agent and the defoaming agent to obtain the second mixed solution; S2, cement, sand, gravel, fly ash, straw ash, silica fume, the third portion of water, and polypropylene solution are mixed in order, placed in a pan mixer, and stirred for 1 min; then cocamidopropyl betaine modified fiber and maleic acid modified attapulgite are added, stirred for 2-4 min, and then the first portion of the mixed solution prepared in step S1 is added, stirred for 3-5 min, and the third portion of the mixed solution is prepared; S3, add the activator to the third mixed solution, stir evenly for 3-5 minutes, and obtain the fourth mixed solution; S4. Add the second mixed liquid to the fourth mixed liquid, stir for another 23 minutes until the mixture is uniform, discharge the mixture to obtain a concrete mixture, and shape and cure the concrete mixture to obtain the ultra-high performance premixed green concrete.

Citation Information

Cited By

  • Waste residue cemented composite material and preparation method thereof

    CN121292870A